2016
DOI: 10.1021/acs.jpcb.6b08109
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Hydrogen-Bonding Partners of Cysteine: Implications for Regulating Cys Functions

Abstract: The hydrogen-bonding interactions of cysteine, which can serve as a hydrogen-bond donor and/or acceptor, play a central role in cysteine's diverse functional roles in proteins. They affect the balance between the neutral thiol (SH) or thiolate (S) and the charge distribution in the rate-limiting transition state of a reaction. Despite their importance, no study has determined the preferred hydrogen-bonding partners of cysteine serving as a hydrogen-bond donor or acceptor. By computing the free energy for displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 55 publications
3
83
0
Order By: Relevance
“…In particular, the , 3c, 3d), which was also predicted by previous docking studies and which is fully consistent with the longer hydrogen bonds that are known to involve sulphur atoms. 16 Interestingly, careful inspection of the electron density showed that the side chain of Cys172 exists in a double conformation (Figures 3b, 3c, 3d) and by using the program PHENIX 17 we refined the occupancy values for the two rotamers of Cys172 in each of the three structures. This resulted to be 0.5 in the case of the complex with inhibitor 1, whereas for the structures with 2 and 3…”
Section: Structures Of Human Mao-b In Complex With Chromone Inhibitorsmentioning
confidence: 99%
“…In particular, the , 3c, 3d), which was also predicted by previous docking studies and which is fully consistent with the longer hydrogen bonds that are known to involve sulphur atoms. 16 Interestingly, careful inspection of the electron density showed that the side chain of Cys172 exists in a double conformation (Figures 3b, 3c, 3d) and by using the program PHENIX 17 we refined the occupancy values for the two rotamers of Cys172 in each of the three structures. This resulted to be 0.5 in the case of the complex with inhibitor 1, whereas for the structures with 2 and 3…”
Section: Structures Of Human Mao-b In Complex With Chromone Inhibitorsmentioning
confidence: 99%
“…In the analysis of cysteine SNO sites, we should also take into account the capability of the cysteine side chain to be involved in hydrogen bonds and how the substitution of the SH group with SNO can affect the native hydrogen bond network. Cys can serve as a hydrogen bond (HB) donor when protonated (SH) as well as a HB acceptor in both protonated and deprotonated states (S − ) ( 144 ).…”
Section: Computational Structural and Chemical Studies Of Smentioning
confidence: 99%
“…The properties of molecules and reactions involving H 2 S and other sulfur-containing molecules have solicited few investigations since the 1970s. [7][8][9][10] Despite the prevalence and importance of these attractive SH interactions, particularly in biochemical systems containing cysteine residues [11][12][13][14][15][16] or other thiolcontaining biomolecules, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] the homogeneous and heterogeneous S analogues of (H 2 O) 2 depicted in Figure 1 have received comparatively little attention. Investigations into the homogeneous (H 2 S) 2 and heterogeneous H 2 O/H 2 S dimers provide insight into interactions with sulfur-containing molecules as well as accurate energetics and vibrational signatures to compare with the H 2 O dimer.…”
Section: Introductionmentioning
confidence: 99%